2019
DOI: 10.3892/ol.2019.10502
|View full text |Cite
|
Sign up to set email alerts
|

Mixed adenoendocrine carcinoma in the extrahepatic biliary tract: A case report and literature review

Abstract: Neuroendocrine neoplasm (NEN) comprises a group of tumors that exhibit neuroendocrine phenotypes. NEN is subclassified into neuroendocrine tumor (NET), neuroendocrine carcinoma (NEC) and mixed adenoendocrine carcinoma (MANEC), based on histopathological parameters. NEN in the extrahepatic biliary tract (EHBT) is uncommon. Little is known about its clinicopathological features and prognostic indicators. The present study presented a case of MANEC in the distal common bile duct (CBD) and reviewed previous cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…The quantitative composition of the primary tumour was described in 36 studies (n = 294) [12,15,17,19,21,[23][24][25]27,29,30,34,36,[39][40][41]45,46,[48][49][50][52][53][54]56,57,59,65,73,74,80,82,[84][85][86]92]; the two components were present in equal proportion in 27.9% (n = 82) of cases, whereas in the remaining 72.1% one of the two histologies was predominant; the neuroendocrine component in 42.2% (n = 124), the non-neuroendocrine component in 29.9% (n = 88).…”
Section: Clinical-pathological Characteristics Treatment Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantitative composition of the primary tumour was described in 36 studies (n = 294) [12,15,17,19,21,[23][24][25]27,29,30,34,36,[39][40][41]45,46,[48][49][50][52][53][54]56,57,59,65,73,74,80,82,[84][85][86]92]; the two components were present in equal proportion in 27.9% (n = 82) of cases, whereas in the remaining 72.1% one of the two histologies was predominant; the neuroendocrine component in 42.2% (n = 124), the non-neuroendocrine component in 29.9% (n = 88).…”
Section: Clinical-pathological Characteristics Treatment Modalitiesmentioning
confidence: 99%
“…Interestingly, in 43 studies (n = 61) where more than one diagnostic sample was available [11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]30,[32][33][34][36][37][38][39][41][42][43][44][45][46][47]49,50,53,55,[59][60][61][62]64,65,96], the initial diagnosis from the first sample collected (either cytological or histological) was in keeping with MiNEN or suspicion of MiNEN in 36.1% (n = 22) of cases, adenocarcinoma in 36.1% (n = 22), poorly differentiated neuroendocrine carcinoma in 21.3% (n = 13), and well differentiated neuroendocrine tumour in 6.6% (n = 4).…”
Section: Clinical-pathological Characteristics Treatment Modalitiesmentioning
confidence: 99%
“…However, Wang HH et al [9] reported that the positivity of CA19-9 was only 15.0%, CA72-4 was 7.5%, CEA was 17.5%, and AFP was 15.0% in primary hepatic neuroendocrine tumors. Furthermore, serum tumor markers are normal in most EBNET G1/G2, but they tend to be higher than normal levels in EBNET G3 or extrahepatic biliary neuroendocrine carcinomas [10][11][12][13][14]. Our patient with the hilar bile duct NETs G1 had serum tumor markers were within normal limits.…”
Section: Discussionmentioning
confidence: 62%
“…We searched the PubMed database using the terms “neuroendocrine carcinoma,” “bile duct,” “endocrine carcinoma,” and “mixed adeno-neuroendocrine carcinoma.” Excluding NECs in the intrahepatic bile duct, gallbladder, and ampulla of Vater, only 24 resected cases of primary EHBD NECs were found [ 3 , 10 32 ]. We briefly summarized these clinical and pathological features (Tables 1 and 2 ).…”
Section: Discussionmentioning
confidence: 99%